Aroma release from carbonated beverages - Yeo, HuiQi (2018)
The effect of monosaccharides (glucose, fructose and galactose) and disaccharides (sucrose and lactose) at different concentrations (10, 20 and 30% w/v) on the static headspace in-vitro release of C4 – C10 aldehydes, ethyl esters and limonene was studied using Atmospheric Pressure Chemical Ionisation–Mass Spectrometry (APCI–MS). An increase in sugar concentration from 0 – 30% w/v resulted in a significant increase in aroma release under static headspace conditions for the majority of the compounds (p < 0.05). This initial study formed the basis for the design of a soft drink model – a system comprised of water, sucrose, acid and aroma compounds representative of an apple style flavouring, namely ethyl butanoate and hexanal. However, the introduction of carbonation to the soft drink model not only added the characteristic fizziness, but also conferred complexity to the system as the diffusion of carbon dioxide from the liquid-gas interface and the formation of effervescence could affect aroma release under the dynamic conditions of beverage consumption. In fact, it was found that the introduction of carbonation resulted in a significant decrease in in-vivo aroma delivery during breath-by-breath analysis (p < 0.05). To understand the physical mechanisms behind aroma release from the beverage matrix, the effect of sugar on the kinetics of the matrix components, namely water, aroma compounds and carbon dioxide, was explored. An increase in sugar concentration from 0 – 30% w/v resulted in a significant decrease in water activity (p < 0.05), which accounted for the significantly slower rate of self-diffusion of aroma compounds (p < 0.05), measured using Diffusion-Ordered SpectroscopY (DOSY)–Nuclear Magnetic Resonance (NMR) spectroscopy. No significant effect of sugar on carbon dioxide volume flux was found (p > 0.05).